Invariance of the Trait Emotional Intelligence Construct Across Clinical Populations and Sociodemographic Variables - Pérez-Díaz, Pablo Alejandro; Manrique-Millones, Denisse; García-Gómez, María; Vásquez-Suyo, Maria Isabel; Millones-Rivalles, Rosa; Fernández-Ríos, Nataly; Pérez-González, Juan-Carlos; Petrides, K. V. (Frontiers in Psychology, 2022)
Recent research has shown that cultural, linguistic, and sociodemographic peculiarities influence the measurement of trait emotional intelligence (trait EI). Assessing trait EI in different populations fosters cross-cultural research and expands the construct’s nomological network. In mental health, the trait EI of clinical populations has been scarcely researched. Accordingly, the present study examined the relationship between trait EI and key sociodemographic variables on Trait Emotional Intelligence Questionnaire (TEIQue-SF) datasets with mental health care patients from three different Spanish-speaking countries. Collectively, these datasets comprised 528 participants, 23% from Chile (120), 28% from Peru (150), and 49% from Spain (258). The sociodemographic variables we used for trait EI comparisons were Gender, Age, Educational Level, Civil Status, and Occupational Status. Analyses involved Multigroup Exploratory Structural Equation Modelling (to test measurement invariance) and ANCOVAs. Our results revealed significant between-country differences in trait EI across the studied sociodemographic variables as well as interactions between these variables. Measurement invariance across the datasets was attained up to the scalar level regarding gender and education (i.e., strong invariance), although analyses on age, civil status and occupation displayed non-invariance. The resultant psychometric evidence supports the suitability of the TEIQue-SF for the accurate cross-cultural assessment of trait EI in mental health settings. It also highlights the importance of incorporating trait emotional intelligence into extant psychotherapeutic frameworks to enhance non-pharmacological treatment efficacy.